1993
DOI: 10.1200/jco.1993.11.11.2150
|View full text |Cite
|
Sign up to set email alerts
|

Combined radiation and chemotherapy for invasive transitional-cell carcinoma of the bladder: a prospective study.

Abstract: This neoadjuvant chemoradiotherapy combination, easy to implement and well tolerated even in elderly patients, provides a high complete response rate. It may prove to be effective in inoperable patients and may be proposed as conservative treatment in patients with a complete response to the initial course of chemoradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
108
0
13

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(128 citation statements)
references
References 27 publications
7
108
0
13
Order By: Relevance
“…However, insufficient local tumor control has been previously reported using this management approach (8). Many patients unfit for surgery will suffer from ongoing tumor-related symptoms (pain, urgency, hematuria).…”
Section: Discussionmentioning
confidence: 99%
“…However, insufficient local tumor control has been previously reported using this management approach (8). Many patients unfit for surgery will suffer from ongoing tumor-related symptoms (pain, urgency, hematuria).…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] Conversely, one series reported that all patients who achieved a CR after radiotherapy (RT) with concurrent cisplatin and 5-FU were pT0 on immediate cystectomy. 50 Although studies report differing frequencies of residual disease after cytotoxic agents (either radiation or chemotherapy), there is consensus that the rate is lower for patients who present with T2 disease versus T3 disease, which should be considered when proposing a bladder-sparing approach.…”
Section: Bladder Preservationmentioning
confidence: 99%
“…5 One of the clearest indications of the potential for chemoradiotherapy came from the University of Paris, where the concurrent chemoradiotherapy approach (as a planned preoperative approach) did not identify any residual disease at cystectomy in the first 18 patients. 6 These results led to a prospective study of selective bladder presentation using a trimodality strategy. 7 The University of Erlangen reported the results of its trimodality treatment in 2002.…”
Section: Bladder Preservationmentioning
confidence: 99%
“…6 These results led to a prospective study of selective bladder presentation using a trimodality strategy. 7 The University of Erlangen reported the results of its trimodality treatment in 2002. 8 In this protocol, patients completed the full course of chemoradiotherapy and underwent transurethral resection of bladder cancer (TURBT) restaging at 6 weeks to 8 weeks and salvage cystectomy for recurrence.…”
Section: Bladder Preservationmentioning
confidence: 99%
See 1 more Smart Citation